Modelo de quatro férmions e anomalias com extensão de Horava-Lifshitz - Costa Filho, Rubens Mário Moreira da (2019)
In this thesis we studied the Horava-Lifshitz formalism and its application to quantum field theories. In the first half of the text we performed a literature review about the Horava model of quantum gravity and discuss the basics advantages of this proposition ralated with the Lifshitz scaling method. In sequence, we apllied this method to a four fermion model of dynamical generation of the electromagnetic field, where we showed the restoration of covariance, when the critical exponent z is one, and the emergence of a spontaneous symmetry breaking when z = 3, still unpublished in the literature. In the second half of the present work we studied a version of the quantum electrodynamics modified by the Horava-Lifshitz formalism, with Lifshitz scaling exponent z = 3, through the method of derivative expansion. We analyzed the radiative corrections and we got with this the generation of free Maxwell action. Lastly, we investigated the possibility of Adler Bell Jackiw (ABJ) anomaly arising in this version of quantum electrodymamics, also with derivative expansion.